Balancing Discipline and Compassion: An Exploratory Study on Islamic Parenting Styles - Lubna Lutfia (Islamic Counseling and Parenting Journal, 2025)
Parenting styles significantly influence child development, yet Muslim parents often struggle to balance Islamic disciplinary principles with compassionate child-rearing. This exploratory mixed-methods study examines how Islamic parenting styles integrate discipline and compassion, and their impact on child outcomes. Data was collected from 200 Muslim parents in Indonesia and Malaysia through surveys (adapted Parenting Styles and Dimensions Questionnaire) and in-depth interviews with 30 participants. Quantitative analysis revealed three dominant parenting styles: authoritative Islamic (62%), authoritarian (28%), and permissive (10%). The authoritative Islamic style showed the strongest positive correlations with children's emotional regulation (r = 0.53, p < 0.01), religiosity (M = 4.2/5), and parent-child communication (M = 4.5/5). Qualitative themes highlighted "Discipline with Mercy" through Qur'anic guidance and Prophetic examples, though cultural misinterpretations led some parents toward excessive strictness. Findings align with Keshavarzi and Haque's (2013) adab-based parenting model while challenging universal applications of Western parenting theories (Darling & Steinberg, 1993). The study underscores the effectiveness of Sunnah-inspired balanced parenting and identifies gaps in culturally adapted Islamic parenting education. Practical implications include developing faith-based parenting programs that integrate psychological insights with Islamic principles. Future research should employ longitudinal designs to assess long-term child outcomes across diverse Muslim communities.